Tsao Hsiu-wen, a women commune member in Chinshan County near Shanghai, creating a painting in praise of the rural barefoot doctors
Tsao Hsiu-wen, a women commune member in Chinshan County near Shanghai, creating a painting in praise of the rural barefoot doctors.